2020
DOI: 10.1177/0004867420950819
|View full text |Cite
|
Sign up to set email alerts
|

The impact of torture on interpersonal threat and reward neurocircuitry

Abstract: Objective: Torture adversely influences emotional functioning, but the neurophysiological mechanisms underpinning its impact are unknown. This study examined how torture exposure affects the neural substrates of interpersonal threat and reward processing. Methods: Male refugees with ( N = 31) and without ( N = 27) torture exposure completed a clinical interview and functional magnetic resonance imaging scan where they viewed fear, happy and neutral faces. Between-group activations and neural coupling were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…These findings complement existing task-related and structural MRI studies, although we note that this is the first study to observe resting-state network functioning differences in torture survivors. For example, a task-related fMRI study observed stronger lateral prefrontal cortical (part of the CEN)—hippocampus coupling during threat face processing in male torture survivors compared to non-torture survivors, as moderated by level of non-torture PTE exposure [ 26 ]. Other structural brain studies focusing on childhood maltreatment have demonstrated that dorsolateral prefrontal cortex volume diminishes following trauma [ 61 ]—a finding that is consistent with studies in torture survivors that have demonstrated grey matter volume reductions across the brain including the prefrontal cortex [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings complement existing task-related and structural MRI studies, although we note that this is the first study to observe resting-state network functioning differences in torture survivors. For example, a task-related fMRI study observed stronger lateral prefrontal cortical (part of the CEN)—hippocampus coupling during threat face processing in male torture survivors compared to non-torture survivors, as moderated by level of non-torture PTE exposure [ 26 ]. Other structural brain studies focusing on childhood maltreatment have demonstrated that dorsolateral prefrontal cortex volume diminishes following trauma [ 61 ]—a finding that is consistent with studies in torture survivors that have demonstrated grey matter volume reductions across the brain including the prefrontal cortex [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the fact that we did not identify a salience network active in our study. Our findings highlight a possible brain network-based mechanism behind this over-regulation response - that is, increased CEN-DMN dynamic functional connectivity, with possible consequences including emotional rigidity, inflexibility, withdrawal, problems with self-regulation and difficulties responding to positive interpersonal situations [ 62 ], all of which have been observed in torture survivors [ 26 ]. Torture exposure itself may therefore fundamentally alter the way intrinsic networks of the brain—in particular the CEN and DMN—function and connect.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations